A CONCEPTUAL STUDY ON SWABHAVOPARAM VADA IN CONTEXT TO NIDANA PARIVARJANA WITH SPECIAL REFERENCE TO ITS MECHANISM USEFUL IN MADHUMEHA (TYPE 2 DIABETES MELLITUS) (International Journal of Ayurveda and Pharma Research, 2020)
The scientific art of living called as Ayurveda is based upon the basic ancient science of way of living as well as reliable on the philosophical grounds. Ayurveda has its roots in the Philosophical sciences and has its applications. The fundamentals or principles are based upon the experiments which were done by our Acharya so many times. And due to this, these ancient rules and code of conduct are still applicable in this modern world. But modern science wants evidence-based study and hence, so many experiments with well observations, investigations were going on to convince the people of the modern world for the validity of these ancient concepts. So, the concepts of Swabhavoparam Vada (Basic Principle of Ayurveda) with its application must be studied thoroughly. This concept “Swabhavoparam Vada” insists on the Homeostasis or Natural Destruction. According to which disease will subside due to natural destruction phenomenon & maintaining of Dhatu Samya is done. That happens due to the fundamental of “Hetu-Hetorvaratananam” which implies to avoid the causative factors (Nidana Parivarjana) responsible for causing a disease. So, this study is an effort to understand the relationship of Swabhvaoparama Vada & Nidana Parivarjana and how this principle is used in the Madhumeha disease (Type 2 Diabetes Mellitus), which is a metabolic disorder and relied upon the Diet and Lifestyle.